Hemorrhagic Encephalopathy From Acute Baking Soda Ingestion - Hughes, Adrienne (West J Emerg Med, 2016)
Baking soda is a readily available household product composed of sodium bicarbonate. It can be used as a home remedy to treat dyspepsia. If used in excessive amounts, baking soda has the potential to cause a variety of serious metabolic abnormalities. We believe this is the first reported case of hemorrhagic encephalopathy induced by baking soda ingestion. Healthcare providers should be aware of the dangers of baking soda misuse and the associated adverse effects.